(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is considered as world’s most diverse federal structured country. It derives powers from constitution to frame and execute rules and policies. Since its Independence India experimented several governance models for empowering it’s people and balanced regional development. Initially Planning Commission entrusted to frame developmental plans which was replaced by NITI Aayog. When we compare the overall development of India, many states are lagging behind in the parameters of development.